Examining the Implementation of Health-Related Social Need (HRSN) Screenings at a Pediatric Community Health Center - Thomas W. Gray; Laura J. Podewils; Rasulo M. Rasulo; Randie P. Weiss; Margaret M. Tomcho (SAGE Publishing, 2023)
Introduction: Social determinants of health (SDoH) influence health outcomes and screening for health-related social needs (HRSN) is a recommended pediatric practice. In 2018, Denver Health and Hospitals (DH) implemented the Accountable Health Communities (AHC) model under the Centers for Medicare and Medicaid Services (CMS) and began using the AHC HRSN screening tool during selected well child visits (WCVs) at a DH Federally Qualified Health Center (FQHC). The current evaluation aimed to examine the program implementation and identify key lessons learned to inform the expansion of HRSN screening and referral to other populations and health systems. Methods: Patients who completed a WCV between June 1, 2020 and December 31, 2021 (N = 13 750) were evaluated. Frequencies and proportions were used to describe patient characteristics of those that had a WCV, were screened, and received resource information. Multivariable logistic regression models with odds ratios (OR) and 95% confidence intervals (CI) were used to determine the association between patient characteristics and completing HRSN screening and provision of resource information. Results: The screening tool was completed by 80% (n = 11 004) of caregivers bringing children to a WCV at the DH Westside Clinic, with over one-third (34.8%; n = 3830) reporting >1 social need. Food insecurity was the most common concern (22.3%; n = 2458). Non-English, non-Spanish (NENS) speakers were less likely to be screened (OR 0.43, 95% CI 0.33, 0.57) and less likely to report a social need (OR 0.59, 95% CI 0.42, 0.82) than speakers of English, after adjusting for age, race/ethnicity, and health insurance. Conclusions: A high rate of screening indicates feasibility of administering HRSN screenings for pediatric patients in a busy FQHC. More than a third of patients reported one or more social needs, underscoring the importance to identity these needs and the opportunity to offer personalized resources. Comparatively lower rates of screening and potential underreporting among NENS may be indicative of the availability and acceptability of current translation procedures as well as how the tool translates linguistically and culturally. Our experience highlights the need to partner with community organizations and involve patients and families to ensure SDoH screening and care navigation is part of culturally-appropriate patient-centered care.